Responsible management education in UK business schools: Critically examining the role of the United Nations Principles for Responsible Management Education as a driver for change. Issue 4 (September 2015) - Burchell, Jon; Kennedy, Steve; Murray, Alan
As examinations of the ethics of business practice have increased so too have questions regarding the role of business schools. A key aspect of this re-evaluation has been the emergence of the United Nations Principles for Responsible Management Education, reflecting the growing emphasis upon 'soft regulation' and voluntary action within new governance frameworks around responsible business practice. This article focuses upon the changing nature of responsible management education within UK business schools and examines the potential role of Principles for Responsible Management Education in shaping these developments. The article examines the findings of two surveys of responsible management education conducted in 2006/2007 and 2009/2010, and qualitative data derived from case studies of five Principles for Responsible Management Education signatory schools. The article questions whether there is any direct evidence for Principles for Responsible Management Education as a driver of curriculum change. It suggests that its primary impact may lie with its facilitative capacity and the ability of active faculty members in utilising this capacity.